DMMR status and synchronous lesions predicts metachronous lesions after curative resection for rectal cancer - Chen, Xijie; Chen, Junguo; Xu, Liang; Lin, Dezheng; Hong, Xiaoling; Peng, Junsheng; He, Xiaowen; Hu, Jiancong (Frontiers in Surgery, 2025)
BackgroundThere are no established standard colonoscopy surveillance protocols for patients after curative rectal cancer resection. We investigated the predictive factors for colorectal neoplasms during surveillance colonoscopies to identify patients who are at risk of developing metachronous neoplasms in the residual colorectum.MethodsThis was a single-center, retrospective study that included patients with diagnosis of rectal carcinoma who had undergone curative resection from October 2012 to June 2018. Clinicopathological variables were analyzed by logistic regression analysis to identify risk factors independently associated with metachronous neoplasms in patients that underwent curative rectal cancer surgery.ResultsIn all, 554 patients were included in the analysis. Deficient mismatch repair (dMMR) status was recorded in 20 (3.6%) patients. At the surveillance colonoscopies, 118 patients (21.3%) had metachronous neoplasms while 169 patients (30.5%) had metachronous polyps. The median time interval between index colonoscopy and the last surveillance colonoscopy was 736.5 (476.75–1,082.25) days. Univariable and multivariable analysis showed dMMR status, synchronous adenomas/polyps, surveillance time > 3, and longer surveillance period patients were significant risk factors for development of metachronous lesions; in subgroup analysis, we also found that among rectal cancer patients with synchronous adenomas, adenomas located in the left colon and rectum, and longer surveillance period were independent risk factors for detecting metachronous adenomas.ConclusionsThis study underscored the importance of extended follow-up protocols and targeted surveillance for identifying and managing metachronous lesions in dMMR rectal cancer patients, especially with synchronous adenomas. Further prospective, multicenter studies are needed to validate these results.